2014
DOI: 10.2478/s11536-013-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in severe acute pancreatitis

Abstract: AbstractAcute pancreatitis (AP) is a local inflammatory response with systemic effects and an adverse evolution in 20% of cases. Its mortality rate is 5–10% in sterile and 15–40% in infected pancreatic necrosis. Infection is widely accepted as the main reason of death in AP. The evidence to enable a recommendation about antibiotic prophylaxis against infection of pancreatic necrosis is conflicting and difficult to interpret. Up to date, there is no evidence that supports the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
2
0
3
Order By: Relevance
“…The rationale for considering antibiotics in AP relate(s) to concern(s) of infection and they are often prescribed in the presence of sepsis with pancreatic necrosis. 28,41 Antibiotics known to readily penetrate necrotic tissues such as carbapenems, quinolones, and metronidazole have all been demonstrated to reduce morbidity and mortality in necrotizing pancreatitis. 42 Here in this current study, we noted disparate types of antibiotics prescribed to treat concurrent systemic infection(s) among the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for considering antibiotics in AP relate(s) to concern(s) of infection and they are often prescribed in the presence of sepsis with pancreatic necrosis. 28,41 Antibiotics known to readily penetrate necrotic tissues such as carbapenems, quinolones, and metronidazole have all been demonstrated to reduce morbidity and mortality in necrotizing pancreatitis. 42 Here in this current study, we noted disparate types of antibiotics prescribed to treat concurrent systemic infection(s) among the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most studies have shown that the use of prophylactic antibiotics to prevent infection in all acute pancreatitis cases shows no benefit, although some specialists still recommend the use of prophylactic antibiotics in ANP. 18 Infection is a prevalent complication, especially in the ANP type. Inoculation of germs in the necrosis of the pancreas and peripancreatic can occur quickly.…”
Section: Discussionmentioning
confidence: 99%
“…dad; se ha mostrado disminución en la incidencia de estas complicaciones en los pacientes que han recibido este tipo de profilaxis, sin lograr estandarizarla incluso en pacientes con pancreatitis severa (4,8). En relación con el inicio de antibioticoterapia de amplio espectro de carácter terapéutico, múltiples estudios y guías de práctica clínica recomiendan los carbapenémicos como la mejor opción por su alta penetrancia en el tejido pancreático y su influencia en la reducción de la mortalidad; además, consideran tener en cuenta indicaciones claras para la instauración en este tipo de pacientes, entre las que se mencionan necrosis pancreática >30 %-40 % por TAC, aislamiento microbiológico de colección peripancreática y mala respuesta clínica en pacientes con pancreatitis severa.…”
Section: Conclusionesunclassified
“…En relación con el inicio de antibioticoterapia de amplio espectro de carácter terapéutico, múltiples estudios y guías de práctica clínica recomiendan los carbapenémicos como la mejor opción por su alta penetrancia en el tejido pancreático y su influencia en la reducción de la mortalidad; además, consideran tener en cuenta indicaciones claras para la instauración en este tipo de pacientes, entre las que se mencionan necrosis pancreática >30 %-40 % por TAC, aislamiento microbiológico de colección peripancreática y mala respuesta clínica en pacientes con pancreatitis severa. En el presente estudio, la incidencia de pancreatitis severa fue del 17 %; sin embargo, el 63 % de los pacientes recibió tratamiento antibiótico (principalmente ampicilina sulbactam), seguido por carbapenémicos; esto puede explicarse por la principal causa de los diferentes casos, dado por una etiología biliar, ya que en nuestro medio es muy frecuente la presentación de colecistitis aguda grados II y III asociadas con episodios de pancreatitis que, según el protocolo institucional, ameritan el inicio de cubrimiento antibiótico (8).…”
Section: Conclusionesunclassified